On the Pairs of Shafts in the Pyramid of Khufu as Means for the Ascent to the Akhet - Miatello, Luca.
The shafts in the pyramid of Khufu have been investigated by robots in several projects. Mason’s marks in red ink at the end of the southern shaft of the “Queen’s Chamber” can be read as the hieratic number 121 (cubits), which would indicate the shaft’s length. Precise measurements were planned for the pyramid superstructure and its architectural elements. This paper shows that the shafts represent paths of the solar circuit, which would have led the king’s immaterial components to the akhet. The model is highly coherent, and all of its features are discussed, as the shape of the inner step pyramid, the sharp turns of 45° in the northern shafts, and the two metal pins inserted into a blocking slab at the end of each lower shaft. doi: http://dx.doi.org/10.5913/jarce.56.2020.a008